Los niños de la Transición : nuevos paradigmas autobiográficos en la literatura española de la última década - Concepción Martín Huertas (Amnis)
Although in recent years many scholars talk about a period of « memory crisis », with the advent of the new century –and more noticeably since the last decade– there is a new stream in the field of Spanish literature in which personal and collective memories seem to be vindicated by the authors as a source of prestige. I am talking about the recent success of autobiographies and autobiographical novels that have been flooding publishing houses lately. In these texts, the reported memories of the authors, usually born in the 60s are not based on a postmemory exercise, but, into their experiences and their own souvenirs, projecting them into the collective memory of the country.